Differences in emotion modulation using cognitive reappraisal in individuals with and without suicidal ideation: An ERP study. Issue 5 (3rd July 2016) - Kudinova, Anastacia Y.; Owens, Max; Burkhouse, Katie L.; Barretto, Kenneth M.; Bonanno, George A.; Gibb, Brandon E.
Abstract : Difficulties in emotion regulation have been associated with increased suicidal thoughts and behaviours. The majority of studies have examined self-reported use of emotion regulation strategies. In contrast, the current study focused on a direct measure of individuals' ability to use a specific emotion regulation strategy, cognitive reappraisal, using the late positive potential (LPP), an event-related potential component that reflects attention to emotional stimuli. Specifically, the cognitive reappraisal ability of 33 undergraduate students was assessed via an image-viewing task during which the participants had to passively view, increase or reduce their emotions in response to looking at neutral, positive or dysphoric images. We found that participants with a history of suicidal ideation (SI) had significantly higher LPP when asked to reduce negative emotion in response to dysphoric images, compared to individuals with no history of SI. These findings suggest that difficulties with using cognitive reappraisal, specifically to decrease negative affect, might be linked to suicide risk.